Clinical Presentation and Surgical Management of Invasive Ductal Carcinoma Grade III: A Case Report - Pande Putu Sucahaya Pradhana; Tasia Irma Endriani; Anak Agung Ngurah Pretangga (HM Publisher, 2025)
Background: Invasive ductal carcinoma (IDC) is the most common type of breast cancer, accounting for approximately 80% of all cases. This case report describes the clinical presentation, diagnosis, and surgical management of a 52-year-old female with IDC Grade III. Case presentation: A 52-year-old female presented with a palpable lump in her left breast, associated with intermittent pain. She had undergone a left breast biopsy excision surgery three months prior. Physical examination revealed a tender mass in the left breast. Imaging studies and histopathological examination confirmed the diagnosis of IDC Grade III. The patient underwent a modified radical mastectomy (MRM). Conclusion: This case highlights the importance of early detection and prompt surgical intervention in the management of IDC Grade III. MRM remains a cornerstone of treatment for locally advanced breast cancer, offering favorable outcomes and improved quality of life.